Pengaruh Penjemuran terhadap Kenyamanan dan Kinerja Produksi Sapi Peranakan Ongole (The Effects of Sun-Bathing on the Ongole Crossbred Cattle’s Comfort and Performances) - Panjono (Panjono); Budi Prasetyo Widyobroto; Bambang Suhartanto; Endang Baliarti (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
This experiment was conducted to observe the effects of sun-bathing on the Ongole Crossbred cattle’s comfort and performances. Eight heads of 1.5–2 years aged Ongole crossbreed bulls were divided into two groups. All of cattle were white in color. The first group was sun-bathed at 07.00–11.00 am. The second group (control) was raised in the barn whole day. The experiment was held for 90 days. The data collected were environmental conditions (air temperature and humidity, wind speed, and light intensity), physiological conditions, behaviors, feed intake, digestibility, average daily gain and feed conversion. The data was analyzed by student-t test. The result showed that there were no significant differences on humidity, win speed, and light intensity in both places at 07.00–11.00 am. The temperature on the sunbathing place at 09.00 am. was significantly higher (P<0.05) than that in the barn. The pulse rate on the second group was higher (P<0.01) than the first group. There were no significant differences of rectal temperature and respiration frequency on both groups. There were no significant differences behaviors except ruminating duration of the first group was longer (P<0.01). There were no significant differences on feed intake,digestibility, average daily gain, and feed conversion on both groups. It was concluded that sun-bathing gave comfortable environment for cattle, but did not affect on the cattle’s performance.(Key words: Cattle, Sun-bathing, Comfort, Performance)